The use of slang in the speech of students of a school in the rural area in the municipality of Macaíba – RN (Research, Society and Development, 2021)
This article aims to analyze the use of slang by students from a rural school in the municipality of Macaíba, Rio Grande do Norte, taking into account the light of Alkmim (2001), some extralinguistic variables, to observe the occurrence or not of this type of linguistic variation, such as: the gender of the students, the age, the economic situation and the social context in which this type of language is used. In our discussions, we also resorted to theorist William Labov (2008), as well as other important scholars who helped to problematize the research results. The methodology applied was descriptive, which is characterized by a cross-sectional view with a quali-quantitative approach. Variables were presented in graphs, tables, relative frequency and percentage. The analyzes were conducted using Excel and OriginPro 8.5 and reveal that female individuals were more active in the use of slang, although this result contradicts the findings of other scholars with whom we dialogued in our discussions. When we look at the age group variable, we find that younger students are also in evidence when using e slang in their daily lives. With regard to the variable of economic and financial situation of students, we conclude that the less favored social class is the one that most uses slang in their daily lives. Finally, we observe that some variables determine or not the use of slang in the researched context.